Hubungan Antara Status Gizi dengan Kondisi Fisik Atlet pada Pemain Sepak Bola Putra Usia 10-12 Tahun Klub SSB Putra Asri Gemolong - Wisnu Mahardika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the relationship between nutritional status and the physical condition of athletes in male soccer players aged 10-12 years at the SSB Putra Asri Gemolong club. The research method used is the correlational method. This research was conducted at SSB Putra Asri Gemolong and this research was carried out from August to September 2022. The sample for this research was 30 people. Data collection techniques in this study used tests and measurements. Quantitative data analysis was assisted by the SPSS application version 25. The results showed that tests of nutritional status and physical condition of athletes on male soccer players aged 10-12 years at the SSB Putra Asri Gemolong 2022 club, namely the nutritional status test showed a